How Successful the Community Conservation Partnerships Empowering the Local Community in Lore Lindu National Park, Indonesia? - Sudirman Daeng Massiri; Golar; Hamka; Hasriani Muis; Naharuddin; Adam Malik (Forest and Nature, 2025)
The community-based conservation partnership (CCP) implemented in Lore Lindu National Park (LLNP) is a community empowerment policy that provides legal access to local communities for forest utilization within the conservation area while strengthening their capacity for economic improvement. This policy strategy aims to support the preservation of conservation area ecosystems while simultaneously supporting the economic well-being of communities surrounding the forest. This study evaluates the performance and effectiveness of CCP in LLNP, focusing on their impact on conservation area functionality and local economic development. The research was conducted in 56 villages surrounding LLNP that have implemented conservation partnerships with park management since 2018. Using structured interviews, in-depth interviews, and focus group discussions, data were collected from relevant stakeholders. The study applied quantitative and qualitative approaches, including Likert-scale assessments and Mann-Whitney U statistical analysis, to evaluate CCP performance across different management areas. The findings reveal that the CCP program has contributed to improving the functionality of the conservation area through participatory conservation and monitoring initiatives. However, the program has not yet significantly boosted the local economy. The capacity of the local community to develop enterprises remains limited. The local community’s capacity to develop the enterprise remains limited. The empowerment process implemented by LLNP managers through CCP focused on strengthening individual and organizational capacities. It necessitates policy support from the local government through assistance for programs that strengthen the local economy, incorporation of business development, and reinforcement of marketing networks for locally produced goods.